Czynniki stymulujące powstanie wirtualnego outsourcingu informatycznego - Dziembek, Damian (The Stimulating Factors of Virtual Outsourcing on Information Systems, 2007)
Today outsourcing information systems are very popular methods used in enterprises. The paper's aim is a presentation of main factors influencing the rise of new concept of information system outsourcing realization. This new idea of information system outsourcing realization is called virtual outsourcing on information systems. The paper presents the idea of virtual outsourcing on information systems. Next, this article characterized varied factors influencing the rise of virtual outsourcing on information systems. The virtual outsourcing on information systems has chance to become a very interesting conception for new enterprises like virtual enterprises or virtual organizations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (11); 2007; nr 1156, s. 141-157